Management of Adverse Drug Reactions with Suspected Immune Mechanisms in Latin America (2014)
ABSTRACT: Rationale Treatment of drug hypersensitivity reactions is usually managed by general practitioners not specifically trained in Allergology. The situation of patients thus treated in different Latin American countries is described, as evaluated in a first visit to a specialist. Methods A descriptive cross sectional study using a modified ENDA questionnaire was implemented in 18 allergology units from 10 different Latin American countries, reporting patients assisted for hypersensitivity adverse drug reactions in the last year. Severity was graded as mild, moderate and severe. Results 453 patients were evaluated. Skin prick tests were done in 13% of patients, and specific IgE in 8%. Drug provocation tests were performed in 159 patients (35%), being positive in 49. Thirty-six percent of the reactions were mild, 44% moderate and 20% severe; Forty-six percent occurred during the first hour of taking the causative drug, 36% between 1 and 24 hours, and 18% after 24 hours. Fifty-seven percent were treated in the ED, 20% by an allergist, 8% by a general practitioner, 6% were self medicated, and 7% received no medication. Forty-five percent of the patients received systemic steroids and antihistamines, 24% antihistamines, and 10% only systemic steroids. Eighty-nine patients had severe reactions, but only 28 received epinephrine. Conclusions More than half of the reactions were treated in the ED, antihistamines were given in 2/3 cases, and steroids in more than half. Epinephrine was administered only in 31% of the patients having severe reactions. Medical education oriented to general and emergency care practitioners in Latin America should focus on this topic.